Los felices años veinte de Felipe Fox-trot, traducción y creación en la obra de Felipe Pinglo Alva - Sarmiento Herencia, Rodrigo (2019)
The following paper notices the impact that American popular music, fox-trot in particular, had over Lima’s renowned composer Felipe Pinglo Alva. In spite of linguistic limitations, determined by the ignorance of the language in which the greatest hits that everyone wanted to dance were massively distributed, the new rhythm gave the composer a unique space within his creative spectrum where he could bring in a refreshing aspect of his writing that helped him take over the new north American musical genres and assimilate them into Peru’snational popular music styles.